2016
DOI: 10.4103/2230-8210.183474
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Type 2 Diabetes Individuals and Correlation with Monocyte Chemoattractant Protein1 and Interferon Gamma from Patients Attending a Tertiary Care Centre in Chennai, India

Abstract: Background:Type 2 diabetes mellitus (T2DM) and obesity are associated with changes in gut microbiota and characterized by chronic low-grade inflammation. Monocyte chemoattractant protein-1 (MCP-1) and interferon gamma (IFNγ) are proinflammatory cytokines which play an important role in the development of T2DM. We undertook this study to analyze the gut microbiota of T2DM and nondiabetic subjects and to determine the profile of MCP 1 and IFNγ in the same subjects attending a tertiary care center in Chennai, Tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We also found that the control yogurt itself had a higher content of Enterobacteriaceae , suggesting why these bacteria were enriched in the gut of control yogurt-fed T2D mice. An increased abundance of Gram-negative bacteria is associated with an increased incidence of diabetes [ 40 , 41 ]. This might be because the Gram-negative bacterial cell wall is a rich source of lipopolysaccharide (LPS), which is highly inflammatory [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the control yogurt itself had a higher content of Enterobacteriaceae , suggesting why these bacteria were enriched in the gut of control yogurt-fed T2D mice. An increased abundance of Gram-negative bacteria is associated with an increased incidence of diabetes [ 40 , 41 ]. This might be because the Gram-negative bacterial cell wall is a rich source of lipopolysaccharide (LPS), which is highly inflammatory [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on healthy individuals in the Pakistani population reported that the microbiome of Pakistani individuals is more similar to that of people from Western countries as compared to that of the Indian population [27,30]. Moreover, the microbiomes of obese-T2DM individuals in the Pakistani population revealed an altered composition with an increased abundance of Firmicutes (55.7%), whereas Proteobacteria (58.8%) is reported to dominate the gut microbial diversity of obese-T2DM individuals from India [31]. Furthermore, at the generic level, Prevotella _9 and Eubacterium coprostanoligenes demonstrated a declining trend in the obese-T2DM Pakistani individuals compared to those from India [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the microbiomes of obese-T2DM individuals in the Pakistani population revealed an altered composition with an increased abundance of Firmicutes (55.7%), whereas Proteobacteria (58.8%) is reported to dominate the gut microbial diversity of obese-T2DM individuals from India [31]. Furthermore, at the generic level, Prevotella _9 and Eubacterium coprostanoligenes demonstrated a declining trend in the obese-T2DM Pakistani individuals compared to those from India [31]. This study sets a benchmark for the comparative analysis of obese-T2DM and healthy metagenomic samples in the Pakistani population.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, evidence has accumulated to support a role for the microbiota, including the bacterial communities in the gut and oral cavity, in T2DM patients (Navab-Moghadam et al, 2017;Larsen et al, 2010;Zhang et al, 2018). Not only do T2DM patients have a different microbiota profile from healthy subjects, but alterations in the microbiota are also responsible for immune responses, such as the expression of proinflammatory cytokines (Xiao et al, 2017;Pushpanathan et al, 2016). Both human and animal studies have shown that diet contributes to the composition of the gut microbiota (Egshatyan et al, 2014;Wen & Duffy, 2017), and a gut microbiota signature that promotes intestinal inflammation may exist, thereby promoting the development of T2DM (Wen & Duffy, 2017).…”
Section: Discussionmentioning
confidence: 99%